Imagining a new "abnormal" amidst COVID-19: Seeking guidance from evolutionary anthropology and theology - Serfontein, Bernice (HTS teologiese studies, 2021)
The coronavirus disease 2019 (COVID-19) pandemic is responsible for the large-scale devastation experienced all over the world. This ‘invisible stranger’ interrupting our daily lives is highlighting in a new and acute way the vulnerability of the human race. Life as we knew it is being changed forever. COVID-19 also exposed the injustices embedded in social structures all over the world. What will life with and after COVID-19 look like in South Africa? The pandemic reveals that South Africa is not the fair and just society we hoped for since the transition to a democratic country in 1994. In light of this, we should be preparing ourselves for the new ‘abnormal’ as what seemed normal was problematic and therefore, truly abnormal. Seeking guidance from evolutionary anthropology, this article will explore whether the evolutionary story of Homo sapiens might offer us insights on how to successfully navigate the multiple challenges COVID-19 unmasks and also brings forth. A discussion on the evolutionary history of homo sapiens within the context of niche construction theory reveals that our unique capacity for imagination and creative collaboration made us successful as a species. It is these capacities for imagination and cooperation that might facilitate us in successfully imagining and thereafter living the new ‘abnormal’. In this article, the question of imaging the new ‘abnormal’ will be explored.Contribution: By creatively integrating the perspectives evident in this research, this article explores whether the Prophets of Israel might offer a feasible paradigm to determine coordinates for the imagined new ‘abnormal’ to be a more fair and just society.